Terminal Ileitis: A Rare Complication of Henoch-Schönlein Purpura in Children - Mano,Ana Lia Costa (2021)
Abstract Henoch-Schönlein purpura (HSP) is characterized by nonthrombocytopenic palpable purpura, arthritis or arthralgia, and gastrointestinal and/or renal involvement. Gastrointestinal symptoms are reported in 50%-75% and they are related to a previous group A streptococcal infection in 40%. A healthy 5-year-old girl presented with a three-week history of a recurrent purpuric rash on the lower limbs, arthralgia and angioedema, without renal involvement. During the third relapse, she had severe, diffuse and persistent abdominal pain and bloody stools. An abdominal ultrasound revealed transmural edema of the last ileal segment, compatible with ileitis. She received prednisolone for five days, with full clinical recovery. Antistreptolysin O titer was elevated. The remaining laboratory tests were normal (antinuclear, anti-neutrophil and anti-Saccharomyces cerevisiae antibodies; rheumatoid factor; stool cultures, parasitological examination and viral antigen tests). One month later, an abdominal ultrasound revealed no abnormalities. Terminal ileitis is a very rare complication of HSP in children but has a good prognosis.